Polymorphisms and gene expression of Notch4 in pulmonary tuberculosis - Fang, Weijun; Liu, Hua; Qin, Lianhua; Wang, Jie; Huang, Xiaochen; Pan, Sha; Zheng, Ruijuan (Frontiers in Immunology, 2023)
Tuberculosis (TB) is a serious public health problem to human health, but the pathogenesis of TB remains elusive. To identify novel candidate genes associated with TB susceptibility, we performed a population-based case control study to genotype 41SNPs spanning 21 genes in 435 pulmonary TB patients and 375 health donors from China. We found Notch4 gene rs206018 and rs422951 polymorphisms were associated with susceptibility to pulmonary tuberculosis. The association was validated in another independent cohort including 790 TB patients and 1,190 healthy controls. Moreover, we identified that the rs206018 C allele was associated with higher level of Notch4 in PBMCs from pulmonary TB patients. Furthermore, Notch4 expression increased in TB patients and higher Notch4 expression correlated with the severer pulmonary TB. Finally, we explored the origin and signaling pathways involved in the regulation of Notch4 expression in response to Mtb infection. We determine that Mtb induced Notch4 and its ligand Jagged1expression in macrophages, and Notch4 through TLR2/P38 signaling pathway and Jagged1 through TLR2/ERK signaling pathway. Collectively, our work further strengthens that Notch4 underlay an increased risk of TB in humans and is involved in the occurrence and development of TB , which could serve as a novel target for the host-targeted therapy of TB.